Life-cycle assessment (LCA) of different pretreatment and product separation technologies for butanol bioprocessing from oil palm frond - Nazira, Mahmud; Rosentrater, Kurt A. (MDPI AG, 2019)
Environmental impact assessment is a crucial aspect of biofuels production to ensure that the process generates emissions within the designated limits. In typical cellulosic biofuel production process, the pretreatment and downstream processing stages were reported to require a high amount of chemicals and energy, thus generating high emissions. Cellulosic butanol production while using low moisture anhydrous ammonia (LMAA) pretreatment was expected to have a low chemical, water, and energy footprint, especially when the process was combined with more efficient downstream processing technologies. In this study, the quantification of environmental impact potentials from cellulosic butanol production plants was conducted with modeled different pretreatment and product separation approaches. The results have shown that LMAA pretreatment possessed a potential for commercialization by having low energy requirements when compared to the other modeled pretreatments. With high safety measures that reduce the possibility of anhydrous ammonia leaking to the air, LMAA pretreatment resulted in GWP of 5.72 kg CO2 eq./L butanol, ecotoxicity potential of 2.84 × 10−6 CTU eco/L butanol, and eutrophication potential of 0.011 kg N eq./L butanol. The lowest energy requirement in biobutanol production (19.43 MJ/L), as well as better life-cycle energy metrics performances (NEV of 24.69 MJ/L and NER of 2.27) and environmental impacts potentials (GWP of 3.92 kg N eq./L butanol and ecotoxicity potential of 2.14 × 10−4 CTU eco/L butanol), were recorded when the LMAA pretreatment was combined with the membrane pervaporation process in the product separation stage.